Consciousness : a very short introduction - Blackmore, Susan J. (New York : Oxford University Press, 2005)
A lively introduction that combines the perspectives of philosophy, psychology and neuroscience - written by the top name in the field, Susan Blackmore.
Includes bibliographical references and index.
Keywords: Consciousness; Conscience; SCIENCE -- Cognitive Science